Chemically treated plastic replacing fine aggregate in structural concrete - El-Nadoury, Wegdan W. (Frontiers in Materials, 2022)
Disposing of plastic waste and excessive consumption of siliceous sand are two arising environmental concerns. The employment of plastic-waste as a fractional substitution of fine aggregate in the concrete production is considered an effective solution to hinder both problems. However, the smooth surface of plastic and subsequently the insubstantial plastic-cement bond obstacles the usage of plastic-waste in producing structural concrete. This research assess the effect of improving the surface hydrophilicity and coarseness of polyethylene terephthalate (P.E.T.) on the mechanical-properties of recycled plastic concrete. The Proposed modification of P.E.T-surface is reached through polymer mixing with 5wt% polystyrene(P.S.) and 5wt% P.K.H.H.-phenoxy resin in twin-screw extruder. Three substitution levels; 5%, 20%, and 50% of fine aggregate with treated plastic-particles are investigated. Four mixes with diverse W/C ratio; 0.4, 0.45, 0.5, and 0.6 are used. The target compressive strength was 35 MPa to ensure the production of structural concrete. Outcomes show that the proposed chemical treatment rises the plastic-particles and cement-paste bond, thus enhances the mechanical-properties and durability of the proposed concrete. The highest strengths are achieved by mix with 5% plastic-substitution. Nevertheless, a 20% replacement of sand with treated plastic can be used effectively to produce structural concrete.